The Concept of Islamic Education Management According to Al-Ghazali: A Historical Study and Relevance in the Contemporary Education Context - Arwan Saputra; Elvina Ardiani Bugis; Muslim Afandi (Journal of Practice Learning and Educational Development, 2025)
This study examines the thoughts of Islamic educational management according to Imam Al-Ghazali (1058–1111 AD), with a historiographical approach. The focus of the study includes managerial components in Al-Ghazali's educational system such as objectives, curriculum, teachers, students, methods, and evaluation based on his main work Ihya' Ulum al-Din. In addition, this study analyzes the relevance of the concept in the context of contemporary education, both in Islamic educational institutions and the national education system. The results of the study show that Al-Ghazali's educational management principles (holistic, character-oriented, spirituality, gradual according to development, and continuous evaluation) are very relevant to answering modern challenges such as moral crises, the need for a character learning approach, and value-based curriculum management.